No difference in outcome between early versus delayed weight-bearing following microfracture surgery of the hip, knee or ankle: a systematic review of outcomes and complications. Issue 1 (13th January 2016) - de SA, Darren; Thornley, Patrick; Niroopan, Gavinn; Khan, Moin; McCarthy, Colm; Simunovic, Nicole; Adamich, John; Jamshidi, Sahab; Farrokhyar, Forough; Peterson, Devin; Musahl, Volker; Ayeni, Olufemi R
Abstract : Importance: Injuries to hyaline cartilage have poor healing potential. Microfracture is often used to treat these lesions; yet, significant variation exists in postoperative rehabilitation protocols. Objective: To systematically examine the evidence on the effects of postoperative weight-bearing status after microfracture surgery. We aimed to ascertain the surgical outcomes and complications associated with patients undergoing microfracture surgery for chondral lesions of the hip, knee or ankle assessing for any difference in outcome between early versus delayed weight-bearing postoperatively. Evidence review: A literature search was performed through five databases (CINHAL, MEDLINE, EMBASE, PubMed and Web of Science) identifying studies addressing weight-bearing following microfracture surgery published between 1990 and March 2015. 2 reviewers conducted a full-text review of eligible studies and the references of these included studies. Inclusion criteria included studies conducted on human subjects who underwent microfracture with a described postoperative weight-bearing protocol; had outcomes data reported and were published in English. Exclusion criteria included review articles, non-surgical studies, technique papers and non-English language studies. The Grades of Recommendation, Assessment, Development and Evaluation (GRADE) criteria were used to evaluate the quality of the evidence among all included studies and data were abstracted and separated by joint—hip, knee and ankle. Descriptive statistics are presented. Findings: We identified and included 46 studies (5 hip studies, 22 knee studies and 19 ankle studies) of very low methodological quality. No included hip studies examined early weight-bearing or any functional protocol assessment. With respect to knee microfracture studies, only 20 of a total of 900 patients followed an early weight-bearing protocol. Given the discrepancy between early and delayed weight-bearing sample sizes available, comparative analyses of outcome scores and complications/reoperations were not pursued. With respect to ankle microfracture studies, there were no differences in functional scores and the rate of complications or reoperations between early and delayed weight-bearing groups. Conclusions and relevance: There is insufficient evidence to draw any meaningful conclusions with respect to differences in functional scores between early versus delayed weight-bearing following microfracture surgery for the treatment of chondral lesions in the hip, knee and ankle.